Phytochemical analysis and cytotoxic effects of kelulut and acacia honey on human gingival fibroblast cells in vitro - Ansari, Moeez (2020)
Synthetic medicine is the most common form of treatment available for alleviation of various health conditions. As with any other substance, despite the benefits of medication, there is a risk of the adverse side effects. Thus, it is prudent to search for more natural alternatives. Honey is a naturally occurring substance which has a history of being used as an allopathic medication for many years. It is rich in various phytochemical compounds, phenolics, acids and minerals which have a positive effect on health. In this study, both honey samples underwent GC-MS analysis to ascertain their composition. Our report by GC-MS detected various compounds within our samples of KH and AH. Overall, 34 compounds were detected in the sample of KH and 32 compounds in AH. Out of these, 12 compounds were identified in KH and 7 compounds in AH by matching the peaks of their mass spectra after ionization by different online libraries. The remainder of the compounds remained unidentified. The identified compounds included flavonoids including furans, pyrans and furfural, larger percentage of HMF in both honey samples and compounds like diterpenes and furfuryl alcohol; as well as glycols in AH and levoglucosan in KH. The presence of flavonoids indicates possible antimicrobial, anti-inflammatory, and antifungal effects of KH and AH, though further study needs to be done to ascertain the exact effect of each compound on HGF cells. The presence of the identified compounds in both honey samples supplement the popularity of their use in general as both honey varieties show promising medical properties and support the popular claim of KH, and AH being used as herbal medicine in various cultures. Human gingival fibroblasts (HGF) were exposed to various concentrations of two types of Malaysian honeys; kelulut honey (KH), acquired from the stingless bees and acacia honey (AH) acquired from sting bees. The effects of different concentrations of each honey type from the lowest 0.015%, to the highest 5% was observed by analysing the viability of HGF cells using MTT assay for 24h, 48h and 72h. The results from the MTT assay showed that the HGF cells demonstrated viability in KH from 0.015% to 3.9% and from 0.015% to 4% in AH. The IC50 values for both KH and AH were determined at 24h, 48h and 72h, and at all time frames remained consistent around 4% for KH and above 4% for AH. This study gave a range for the viability of HGF cells after exposure to KH and AH. HGF cells within 3% concentration of both KH and AH, appear to proliferate effortlessly. This range of viability in both the honey samples can be used to further examine other medically beneficial effects of KH and AH on HGF and other periodontal cells.